Is the response over? The transition from response to recovery in the health sector post-Haiyan - Gocotano, Allison; Geroy, Lester Sam; Alcido, Ma Rowena; Dorotan, Miguel Manuel; Balboa, Gloria; Hall, Julie Lyn (Western Pacific Surveillance and Response, 2015)
The transition period from response to recovery after a disaster occurs with no clear start or endpoint. This paper describes the health sector transition from our perspective for the period three to seven months after Typhoon Haiyan. We observed that while there were landmark dates marking different phases post disaster, the transition period was complicated by different perspectives from different health system actors at different levels. However, some features of continuing progress were observed and these mark a transition from response to recovery. Development of a framework or standard measurement for the transition from response to recovery in the health sector is paramount because this impacts on resources and type of activities needed for long-term planning.